Differential expression of the cellular oncogenes c-src and c-yes in embryonal and adult chicken tissues. Issue 9 (September 1984) - Gessler, Manfred; Barnekow, Angelika
Abstract : The cellular onc - genes c-src and c-yes are expressed very differently during chicken embryonic development. The c-src mRNA and its translational product are detectable at high levels in brain extracts of chicken embryos and adult chickens) whereas muscle extracts show an age-dependent decrease in the amounts of c-src -specific mRNA and pp60 c-src kinase activity. In contrast) the levels of c-yes mRNA in brain, heart, and muscle are relatively low in early embryonic stages and increase later on to values comparable to those found for liver) while in adult animals the pattern of c-yes expression is similar to that of the c-src gene. From the close correlation between the levels of pp60 c-src its enzymatic activity, and its corresponding mRNA at a given stage of development and in given tissues) it appears that the expression of pp60 c-src is primarily controlled at the level of transcription. It is suggested that because of the different patterns of expression) the two cellular oncogenes) c-src and c-yes ) play different roles in cell proliferation during early embryonic stages as well as in ensuing differentiation processes.